3D Printing of Buildings and Building Components as the Future of Sustainable Construction?. (2016) - Hager, Izabela; Golonka, Anna; Putanowicz, Roman
Abstract: The paper presents the state-of-the-art concerning the current achievements in the field of 3D printing of buildings and building components. The 3D printing technologies, comparing to traditional techniques of constructing the buildings, could be considered as environmental friendly derivative giving almost unlimited possibilities for geometric complexity realizations. Two kinds of technologies were described in this paper with pointing to Contour Crafting as a promising technique that may be able to revolutionize construction industry in near future. Numerous advantages of this technology, such as reduction of the costs and time, minimizing the pollution of environment and decrease of injuries and fatalities on construction sites could be cited. Despite many advantages and hopes, some concerns are summarized in the conclusions, as the technology still has many limitations. A brief description of few examples of pioneering usage of 3D printing in construction industry are presented (Canal House in Amsterdam, WinSun company and printing application for building carried out by Skanska company). Creating a model that will be appropriate for 3D printers is possible in many different modelling programs. One of the most popular formats for sharing such models is STL format. In the paper sample models crated in Autodesk Inventor are shown, but also other tools suitable for preparing models for 3D printing are briefly discussed.